2012
DOI: 10.1590/s0100-736x2012000200009
|View full text |Cite
|
Sign up to set email alerts
|

Fatores de risco associados à infecção por Toxoplasma gondii em ovinos e caprinos no estado de Pernambuco

Abstract: This study was conducted to investigate the participation of Toxoplasma gondii in reproductive failure in small ruminants raised in the Litoral/ Zona da Mata and Agreste of the State of Pernambuco, Brazil. Twelve ϐlocks were selected from which 262 samples were collected, 167 from goats and 95 from sheep. Indirect Imunoϐluorescent Antibody Reaction (IFA) technique was used to detect antibodies anti-Toxoplasma gondii. A questionnaire was applied in ϐlocks to identify risk factors associated with infection. Posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
1
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 14 publications
5
14
1
7
Order By: Relevance
“…Similar serological studies conducted in Brazil have also reported seroprevalence values in sheep ranging between 3.7-35.3% SILVA et al, 2003;PINHEIRO JÚNIOR et al, 2009;SOCCOL et al, 2009;PEREIRA et al, 2012;NUNES et al, 2015;SILVA et al, 2015).…”
Section: Introductionsupporting
confidence: 77%
See 3 more Smart Citations
“…Similar serological studies conducted in Brazil have also reported seroprevalence values in sheep ranging between 3.7-35.3% SILVA et al, 2003;PINHEIRO JÚNIOR et al, 2009;SOCCOL et al, 2009;PEREIRA et al, 2012;NUNES et al, 2015;SILVA et al, 2015).…”
Section: Introductionsupporting
confidence: 77%
“…Although production animals like sheep were found to be more susceptible to infection than other species (MILLAR et al, 2008), serological studies have confirmed the distribution of T. gondii infection in sheep with variable percentages (TENTER et al, 2000). The prevalence of seropositive animals found in this study (13.60%) was lower than the results found in other Brazilian states (LANGONI et al, 1999;PINHEIRO JÚNIOR et al, 2009). A previous study pertaining to other regions of Pernambuco showed similar results, with 16.90% of sheep seropositive for T. gondii infection (SILVA et al, 2003).…”
Section: Resultscontrasting
confidence: 54%
See 2 more Smart Citations
“…No município de Guarapuava, Paraná, foi observada uma prevalência de 51,5% e na microrregião de Jaboticabal, São Paulo, 52% de ovinos reagentes a anticorpos contra T. gondii (Romanelli et al, 2007;Lopes et al, 2010). Já com resultados inferiores à presente pesquisa, em um estudo realizado no estado de Pernambuco, foram analisadas 95 amostras de ovinos provenientes das regiões do Litoral, Zona da Mata e Agreste e identificaram 16,2% de positividade (Pereira et al, 2012).…”
Section: Palavras-chaveunclassified